Genome‐Wide Associations of Global Electrical Heterogeneity ECG Phenotype: The ARIC (Atherosclerosis Risk in Communities) Study and CHS (Cardiovascular Health Study). Issue 8 (11 September 0207) - Tereshchenko, Larisa G.; Sotoodehnia, Nona; Sitlani, Colleen M.; Ashar, Foram N.; Kabir, Muammar; Biggs, Mary L.; Morley, Michael P.; Waks, Jonathan W.; Soliman, Elsayed Z.; Buxton, Alfred E.; Biering‐Sørensen, Tor; Solomon, Scott D.; et al.
Abstract : Background: ECG global electrical heterogeneity (GEH) is associated with sudden cardiac death. We hypothesized that a genome‐wide association study would identify genetic loci related to GEH. Methods and Results: We tested genotyped and imputed variants in black (N=3057) and white (N=10 769) participants in the ARIC (Atherosclerosis Risk in Communities) study and CHS (Cardiovascular Health Study). GEH (QRS‐T angle, sum absolute QRST integral, spatial ventricular gradient magnitude, elevation, azimuth) was measured on 12‐lead ECGs. Linear regression models were constructed with each GEH variable as an outcome, adjusted for age, sex, height, body mass index, study site, and principal components to account for ancestry. GWAS identified 10 loci that showed genome‐wide significant association with GEH in whites or joint ancestry. The strongest signal (rs7301677, near TBX3 ) was associated with QRS‐T angle (white standardized β+0.16 [95% CI 0.13–0.19]; P =1.5×10 −26 ), spatial ventricular gradient elevation (+0.11 [0.08–0.14]; P =2.1×10 −12 ), and spatial ventricular gradient magnitude (−0.12 [95% CI −0.15 to −0.09]; P =5.9×10 −15 ). Altogether, GEH‐SNPs explained 1.1% to 1.6% of GEH variance. Loci on chromosomes 4 (near HMCN2 ), 5 ( IGF1R ), 11 (11p11.2 region cluster), and 7 (near ACTB ) are novel ECG phenotype‐associated loci. Several loci significantly associated with gene expression in the left ventricle ( HMCN2 locus—with HMCN2 ; IGF1R locus—with IGF1R ), and atria ( RP11‐481J2.2 locus—with expression of a long non‐coding RNA and NDRG4 ). Conclusions: We identified 10 genetic loci associated with ECG GEH. Replication of GEH GWAS findings in independent cohorts is warranted. Further studies of GEH‐loci may uncover mechanisms of arrhythmogenic remodeling in response to cardiovascular risk factors.